115 RIBOSOMAL P70S6K COORDINATELY CHANGES WITH INTESTINAL AND MUSCLE PROTEIN SYNTHESIS RATES DURING VIRAL DIARRHEA. (1st January 2005) - Rhoads, J. M.; Niu, X. M.; Corl, B.; Harrell, R.; Gatlin, L.; Odle, J.
Abstract : Each year, worldwide, there are ˜ 3 diarrheal episodes per infant, and ˜ 8 in 1000 babies die from diarrhea disease. In the U.S. rotavirus alone causes 3.1 million diarrheal episodes annually, with 125 deaths. Rotavirus produces diarrhea by infecting the tips of intestinal villi, resulting in villus shedding and restitution. During a typical 3-5 day episode, calorie intake and absorption are both reduced ˜ 20%. Recurrent episodes produce malnutrition. The mammalian target of rapamycin (mTOR) has been called the "nutrient sensor" of eukaryotic cells, recognizing ambient concentrations of amino acids. mTOR phosphorylates p70s6k and 4E-BP1, both of which increase the translation of mRNA. Hypotheses: 1. In piglet rotavirus diarrhea p70s6k is activated during intestinal repair. 2. Fasting inactivates p70s6k. Methods: We collected pigs at birth (20-25/group) and fed them full strength formula. Half were inoculated with rotavirus and placed on a 50% diluted diet because malnourished pigs have a more prolonged course of diarrhea, allowing examination of repair. We euthanized pigs at days 1, 3, 5, 11; measured diarrhea score; and harvested intestinal and muscle tissues in RIPA buffer for Western blotting. We used rabbit p70s6k antibody; rabbit phospho-p70s6k antibody, and anti-actin antibody (control). Body weight and diarrhea scores validated the adequacy of infection. Results: Intestinal protein synthesis in vitro increased 1.5-2-fold during infection while muscle protein synthesis decreased concomitantly. Intestinal p70s6k was strongly activated (phosphorylated) d3-5 post-infection while muscle p70s6k was inactivated at d1-3 post-infection. Total p70s6k also increased markedly in the infected intestine, as measured by immunohistochemistry and Western blotting. Feeding markedly activated p70s6k in muscle but not in liver or intestine. When ex vivo infected intestinal segments were incubated with medium with or without additional amino acids, we found that combinations of amino acids or L-arginine alone activated p70s6k. Conclusions: Infectious diarrhea results in increased intestinal protein synthesis, increased intestinal activation of p70s6k, reduced muscle protein synthesis, and reduced muscle activation of p70s6k. Ribosomal p70s6k is not a nutrient sensor in the intestine but is a repair signal. Arginine may contribute to the restitution process in viral diarrhea.